ANALISA BIAYA PEMANFAATAN FLY ASH SEBAGAI MATERIAL DASAR BETON SELF COMPACTING GEOPOLYMER - Chichilya S. P. Sondakh; Stevanny Gumalang; Mickson Pinori (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
The vibratory compaction process to obtain high-quality concrete has difficulties when faced with complex structural models. In the last few decades, research and development of self-compacting concrete (SCC) has been carried out. The application of SCC in Indonesia is still limited because the manufacturing costs are quite high. The composition of cement in SCC is more than conventional concrete, which means it causes higher air pollution. The amount of cement production is directly proportional to the amount of CO2 released into the atmosphere, so the world cement industry makes a major contribution to global greenhouse gas emissions. Several studies have begun to innovate combining SCC and overall cement replacement technology with a pozzolanic material that has cement-like characteristics. One of the alternative materials to replace Portland cement is fly ash, which is a waste material from burning coal in the PLTU. For fly ash to bind like cement, an activator is needed. The mixture of fly ash and activator is known as geopolymer paste, so the combination of these two concrete technologies is called geopolymer self-compacting concrete with fly ash as a base material. In Indonesia, geopolymer self-compacting concrete is still limited in the mix design testing phase, so the authors are interested in knowing the economic review of this type of concrete, and intend to analyze the cost of production of this geopolymer self-compacting concrete using local materials, fly ash from PLTU II Amurang, North Sulawesi Province. The study began with an examination of local materials in North Sulawesi for a concrete mix design. Followed by conducting experimental testing to get the characteristics of fresh concrete and the compressive strength of the concrete. Furthermore, analysis of production costs based on mix-design for 1 m3 of concrete. The workability test of the fresh geopolymer self-compacting concrete with fly ash as a base material through the slump flow method, V-funnel test, and L-Box Shaped test shows that it qualifies the SCC requirements and also produces K-250 quality of concrete. Geopolymer concrete combined with SCC concrete, which has a relatively high cost, results in high production costs of Geopolymer Self Compacting Concrete.